ANALYSIS OF THE INFLUENCE OF FLEXING IN SOCIAL MEDIA ON COMMUNITY LIFE - Roida Pakpahan; Donny Yoesgiantoro (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Flexing or showing off is a new habit that society loves today. Technological factors also influence flexing behavior. We Are Social 2023 states that 167 million Indonesians are active in using social media. In general, flexing is done to legitimize social status through various uploads on TikTok, Instagram Facebook, YouTube and others. This study aims to analyze of the influence of flexing in social media on community life. The results of the study show that luxury content is a favorite of netizens. Even though the luxury that is displayed is not necessarily true. Flexing has a positive influence because flexing can be used for employee branding through linkedIn. Flexing marketing to achieve success in popularity, business and endorsement. However, overall flexing has a more negative influence . Flexing creates consumptive behavior and hedonism. The use of goods is no longer interpreted as fulfilling needs, but rather as a brand or symbol to indicate lifestyle and social status. Sometimes flexing is used as a method of deception. POLRI and related institutions are expected to be more informative, actively monitoring and countering flexing content that has the potential to harm the public. Intelligence is needed in managing information, in the era of information openness, people must be more proficient in social media, filter flexing content so they don't get trapped in FOMO. Actually, flexing is the right of each individual, but it should not reduce the values of life. Minimize flexing behavior by prioritizing achievement.